Carcinome sarcomatoïde: prise en charge thérapeutique et profil pronostique à propos d´une localisation maxillaire inhabituelle (à propos d´un cas) - Sayad, Zahra (Pan Afr Med J, 2021)
Sarcomatoid carcinoma is a rare, aggressive, malignant tumor with a poor prognosis and a very high frequency of recurrence. Carcinoma of the maxillary sinus is extremely rare. We report the case of a 42-year-old woman with left maxillary process. Biopsy revealed aggressive sarcomatoid carcinoma with a lymph-node metastasis. The patient underwent surgical excision, lymph-node dissection followed by radiotherapy with good outcome. The rarity of this site-specific cancer poses a problem of diagnosis and timely management which is still a controversial topic. However, wide surgical excision is the gold standard treatment. This study highlights the anatomoclinical peculiarities and, in particular, the prognostic features of this tumor.